Fathers and their children in the first three years of life : an anthropological perspective - Williams, Frank L'Engle, 1966- (Texas A & M University anthropology series ;, 2019)
"Frank L'Engle Williams examines the anthropological record for evidence of the social behaviors associated with paternity, suggesting that ample evidence exists for the importance of such behaviors for infant survival. Focusing on the first three postnatal years, he considers the implications of father care--both in the fossil record and in more recent cross-cultural research--for the development of such distinctively human traits as bipedalism, extensive brain growth, language, and socialization. He also reviews the rituals by which many human societies construct and reinforce the meanings of socially recognized fatherhood--hormonal, physiological, and social changes incorporated into specific cultural manifestations of paternity. Father care was adaptive within the context of the parental pair bond, and shaped how infants developed socially and biologically. The initial imprinting of socially recognized fathers during the first few postnatal years may have sustained culturally-sanctioned indirect care such as provisioning and protection of dependents for nearly two decades thereafter. In modern humans, this three-year window is critical to father-child bonding--which differs so intrinsically from the mother-child relationship. By increasing the survival of children in the past, present, and quite possibly the future, father care may be a driving force in the biological and cultural evolution of Homo sapiens"--